Recent advances in metal oxide photocatalysts for photocatalytic degradation of organic pollutants: A review on photocatalysts modification strategies - R. S. R., Mohd Zaki; Rohayu, Jusoh; Chanakaewsomboon, Issara; Herma Dina, Setiabudi (Elsevier Ltd, 2023)
Wastewater from industries that predominantly consist of organic pollutants significantly contributes to water pollution and harms the environment, demanding urgent solutions. Among the available wastewater treatment technologies, photocatalysis has garnered considerable interest due to its high efficiency, cleanliness, and sustainability. However, metal oxide photocatalysts, despite extensive study, possess limitations such as agglomeration, rapid electron-hole recombination, and photo corrosion. These limitations hinder the practical design and synthesis of photocatalysts. To address these challenges, researchers have explored various photocatalyst modification approaches, including doping with noble or non-noble metals, crystal facet engineering, physical deposition, dye sensitization, and the implementation of the Z-scheme photocatalyst system. These modifications aim to enhance the catalytic properties of photocatalysts and improve the degradation of organic pollutants. This review article highlights recent advances in the modification strategies of metal oxide photocatalysts for the photocatalytic degradation of organic pollutants. The future prospect and conclusions were also discussed. This review is expected to provide an in-depth understanding of metal oxide photocatalyst development, thus accelerating the evolution of photocatalytic degradation of pollutants.